Effect of Active Carbon of Coffee Robusta Waste (Coffea robusta Lindl.) in Reducing Iron of Peat Water - Dinna Rakhmina; Rizki Mulanova; Haitami Haitami (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2018)
Peat water has a distinctive dark brown or yellow color, low pH, it tastes sour, high organic matter content, high levels of iron and manganese. One of the ways that can be used to reduce the levels of iron in peat water is doing adsorption process by using activated carbon coffee waste because the coffee waste included organic ingredients. The purpose of this research was to identify the influence of the concentration of activated carbon robusta coffee waste (Coffea robusta Lindl.) against the iron levels in peat water. This research uses the draft Posttest-Only Control Group Design. Manufacture of activated carbon robusta coffee waste (Coffea robusta Lindl.) consists of the processes of dehydration, carbonization, and activation, with the results 25.9% of rendemen, 14.05% water content, a rate of 9.9% ash, and iod absorbance 647.19 mg/g. Activated carbon coffee waste added to 100 ml of peat water as much as 3 gr, 4.5 gr, and 6 gr with the stirring speed 400 rpm for 60 minutes obtained early iron levels of 2.75 mg/L and dropped to 1.19 mg/L, 1.02 mg/L, and 0.95 mg/L. Conclusions This study is there is the influence of the concentration of activated carbon robusta coffee waste (Coffea robusta Lindl.) against the iron level of peat water iron and frequency of 6 gr as a concentration of the best efficiency adsorption of 65.4% because it can reduce the levels of iron in 100 ml of peat water from 2.75 mg/L be 0.95 mg/L. By regulation of the Minister of health RI No. 416/Menkes/PER/IX/1990 namely of 1.0 mg/L. Suggestions for further research to improve the heating temperature and concentration of the Activator to obtain active carbon absorption.